Evaluation of the Anti-Adenoviral Activity of ALTANT, an Ozonated Alcohol Disinfectant - Hanaoka, Nozomu; Nojiri, Naomi; Takahashi, Kenichiro; Yoshida, Eiichi; Fujimoto, Tsuguto (Japanese Journal of Infectious Diseases, 2020)
Seven human mastadenovirus (HAdV) species (A–G) are known with more than 100 reported types. HAdV is highly resistant to common hand sanitizers. Epidemic keratoconjunctivitis and pharyngoconjunctival fever are caused by HAdV, which can be explosively transmitted in a confined space, resulting in outbreaks, such as nosocomial infections. Given the absence of an antiviral agent against the HAdV infection, it is important to prevent the spread of the infection by using disinfectants. Ozone has already been well-known for its bactericidal and virucidal effects. ALTANT is an ozonated alcohol preparation developed by E-TECH Co., Ltd. (Kobe, Hyogo, Japan). In this study, we mixed ALTANT with different HAdV types at a ratio of 9:1 and determined HAdV viability after instantaneous reactions for varying periods (flash to 5 minutes) using the TCID50 assay. The assay results demonstrated that the HAdV viability decreased by 1/10 to 1/100 within 1 minute after the reaction; additionally, slight differences in the reactivity were observed among the HAdV types. HAdV viability decreased by a factor of > 4log10, and the virus was eliminated within 3 minutes. This study demonstrated the potent HAdV disinfection effect of ALTANT.